The Johnstown Girls - George, Kathleen, 1943- (Book collections on Project MUSE., 2014)
"The Johnstown Girls is a heartrending tale of twin sisters separated by the 1889 flood in Johnstown, Pennsylvania. Kathleen George masterfully blends a factual history of the flood into her story of two sisters, whose search for each other over the course of one hundred years unfolds after their lives were sent careening down different paths"--